偏微分方程的特征线法

1 篇文章 1 订阅

拟线性情形 ↺

一般步骤 ↺

α(x,u)xu=β(x,u)(1) (1) α ( x , u ) ⋅ ∂ ∂ x u = β ( x , u )

duds=uxdxds(2) (2) d u d s = ∂ u ∂ x ⋅ d x d s

dxds=α(x,u)(3) (3) d x d s = α ( x , u )

duds=β(x,u)(4) (4) d u d s = β ( x , u )

<br/>dxds=α(x,u)duds=β(x,u)(5) (5) { d x d s = α ( x , u ) < b r / > d u d s = β ( x , u )

c=f(x,u)(6) (6) c = f ( x , u )

$\begin{array}{}\text{(7)}& G\left(\mathbit{f}\left(\mathbit{x},u\right)\right)=0\end{array}$

简单例子 ↺

ut+xux=u2,u(x,0)=f(x)(8) (8) ∂ u ∂ t + x ∂ u ∂ x = u 2 , u ( x , 0 ) = f ( x )

dt=dxx=duu2(9) (9) d t = d x x = d u u 2

x=C1et,u=1C2t(10) (10) x = C 1 e t , u = 1 C 2 − t

t=0 t = 0 $t=0$时，有 x=C1,u=1C2=f(C1) x = C 1 , u = 1 C 2 = f ( C 1 ) $x=C_1,u=\frac{1}{C_2}=f(C_1)$，从而解得 C2=1f(C1) C 2 = 1 f ( C 1 ) $C_2 = \frac{1}{f(C_1)}$，因为我们有 C1=xet,C2=u1+t C 1 = x e − t , C 2 = u − 1 + t $C_1 = xe^{-t}, C_2 = u^{-1} + t$，所以代入得到

u1+t=1f(xet)(11) (11) u − 1 + t = 1 f ( x e − t )

u=f(xet)1t×f(xet)(12) (12) u = f ( x e − t ) 1 − t × f ( x e − t )

一般情形 ↺

F(x,u,ux)=0(13) (13) F ( x , u , ∂ u ∂ x ) = 0

https://en.wikipedia.org/wiki/Method_of_characteristics

推导 ↺

$\begin{array}{}\text{(14)}& \mathbit{p}=\frac{\mathrm{\partial }u}{\mathrm{\partial }\mathbit{x}}\end{array}$

0=<br/>Fxdxds+Fuuxdxds+Fpdpds=(Fx+Fup)dxds+Fpdpds<br/>(15) (15) 0 = ∂ F ∂ x ⋅ d x d s + ∂ F ∂ u ∂ u ∂ x ⋅ d x d s + ∂ F ∂ p ⋅ d p d s < b r / > = ( ∂ F ∂ x + ∂ F ∂ u p ) ⋅ d x d s + ∂ F ∂ p ⋅ d p d s < b r / >

dxds=Fp,dpds=FxFup(16) (16) d x d s = ∂ F ∂ p , d p d s = − ∂ F ∂ x − ∂ F ∂ u p

duds=uxdxds=pFp(17) (17) d u d s = ∂ u ∂ x ⋅ d x d s = p ⋅ ∂ F ∂ p

<br/><br/><br/>dxds=Fpdpds=FxFupduds=pFpF(x,u,p)=0(18) (18) { d x d s = ∂ F ∂ p < b r / > d p d s = − ∂ F ∂ x − ∂ F ∂ u p < b r / > d u d s = p ⋅ ∂ F ∂ p < b r / > F ( x , u , p ) = 0

又一个例子 ↺

ut=(ux)2,u(x,0)=f(x)(19) (19) ∂ u ∂ t = ( ∂ u ∂ x ) 2 , u ( x , 0 ) = f ( x )

<br/><br/>dtds=1,dxds=2pxdptds=0,dpxds=0duds=pt2p2x=p2x(20) (20) { d t d s = 1 , d x d s = − 2 p x < b r / > d p t d s = 0 , d p x d s = 0 < b r / > d u d s = p t − 2 p x 2 = − p x 2

u=C22t+f(x+2C2t)(21) (21) u = − C 2 2 t + f ( x + 2 C 2 t )

C2=px=f(x)=f(C3)(22) (22) C 2 = p x = f ′ ( x ) = f ′ ( C 3 )

$\begin{array}{}\text{(23)}& \begin{array}{rl}u=& -t×{f}^{\prime }\left({C}_{3}{\right)}^{2}+f\left(x+2t×{f}^{\prime }\left({C}_{3}\right)\right)\\
=& -t×{f}^{\prime }\left({C}_{3}{\right)}^{2}+f\left({C}_{3}\right)
\end{array}\end{array}$

x=2C2t+C3=2t×f(C3)+C3(24) (24) x = − 2 C 2 t + C 3 = − 2 t × f ′ ( C 3 ) + C 3

C3=x14t(25) (25) C 3 = x 1 − 4 t

u=x214t(26) (26) u = x 2 1 − 4 t

自上而下的过程 ↺

<br/>dxds=αduds=pα(27) (27) { d x d s = α < b r / > d u d s = p ⋅ α

方程组的情形 ↺

(α(x,u)x)u=β(x,u)(28) (28) ( α ( x , u ) ⋅ ∂ ∂ x ) u = β ( x , u )

<br/>dxds=α(x,u)duds=β(x,u)(29) (29) { d x d s = α ( x , u ) < b r / > d u d s = β ( x , u )

10-25
06-03 1万+
10-14 517
10-14
05-15
04-01 2189
08-22 1万+
01-18 588